Entrepreneurship as a Driver of the Digital Transformation - Uma Gunasilan (International Review of Management and Marketing, 2019)
Digital technologies are also affecting the supply and demand of the sector. Apparently, more firms are keen in optimizing the methods of utilizing their assets to foster productivity. Thus, digital technologies are seen as ideal mechanisms for changing the patterns of energy consumption, optimizing asset, fostering cross-industry partnerships, and fostering a greater use of industrial platforms. Adapting open inventions, paradigm accepts that organizations have to utilize the internal ideas and as well as the external ideas and further the internal paths and external paths to market established companies are building up structural programs to harness the power of entrepreneurial.